PENGARUH KEPEMILIKAN ASING, KOMISARIS INDEPENDEN, LEVERAGE DAN KOMITE AUDIT TERHADAP PEMILIHAN AUDITOR PADA PERUSAHAAN SEKTOR INDUSTRI YANG TERDAFTAR DI BEI - Istiqomah Wardani; Poppy Indriani; Septiani Fransisca (Faculty of Economics and Business, 2021)
This study aimed to test whether the influence of foreign ownership, independent commissioners, leverage and audit committee on auditor selections. Using 44 industrial sector companies as populations listed on the Indonesia Stock Exchange from 2014 to 2017. The research hypothesis was tested using logistic regression. The results of the study concluded that foreign ownership, leverage, and audit committees did not affect the selection of auditors, while independent commissioners had a negative effect on the selection of auditors.